Selection for grain yield in sorghum under moisture and nutrient stress environments - Menkir, A.; Ejeta, G. (2003)
Crop breeders in the semi-arid tropics often confront a combination of moisture and nutrient stress in their target production environments. Stability of performance under stress conditions is, thus, a desirable goal for crop improvement. The objectives of these studies were (1) to explore the extent of genetic variability among recombinant inbred lines of sorghum (Sorghum bicolor) in high and low fertility as well as in irrigated and rainfed conditions, and (2) to predict and measure the correlated responses of sorghum yields when selection is exercised in either one environment or a combination of contrasting environments. We evaluated 57 unselected recombinant inbred (RI) sorghum lines. Large differences in yield, height, and maturity were detected among lines in each contrasting environment. Genetic variance and heritability estimates for each trait in each stress environment did not differ significantly from those in the corresponding non-stress environments. For improving yield under stress, indirect selection in high fertility or in the irrigated environment was less efficient than direct selection in the corresponding stress environment (low fertility or rainfed). When indirect selection involved yield combinations from low and high fertility or rainfed and irrigated conditions, at least five lines appeared among the 10 top-ranking lines of each contrasting environment. Thus, greater gain in performance over contrasting environments may be achieved by selecting for yield in more than one environment, rather than by selecting in any single environment.